Impact of diabetes on longevity and disability-free life expectancy among older South African adults: A prospective longitudinal analysis. (March 2023) - Payne, Collin F.; Liwin, Lilipramawanty K.; Wade, Alisha N.; Houle, Brian; Du Toit, Jacques D.; Flood, David; Manne-Goehler, Jennifer
Abstract: Aims: We seek to understand the coexisting effects of population aging and a rising burden of diabetes on healthy longevity in South Africa. Methods: We used longitudinal data from the 2015 and 2018 waves of the "Health and Aging in Africa: A Longitudinal Study of an INDEPTH Community in South Africa" (HAALSI) study to explore life expectancy (LE) and disability-free life expectancy (DFLE) of adults aged 45 and older with and without diabetes in rural South Africa. We estimated LE and DFLE by diabetes status using Markov-based microsimulation. Results: We find a clear gradient in remaining LE and DFLE based on diabetes status. At age 45, a man without diabetes could expect to live 7.4 [95% CI 3.4 – 11.7] more years than a man with diabetes, and a woman without diabetes could expect to live 3.9 [95% CI: 0.8 – 6.9] more years than a woman with diabetes. Individuals with diabetes lived proportionately more years subject to disability than individuals without diabetes. Conclusions: We find large and important decrements in disability-free aging for people with diabetes in South Africa. This finding should motivate efforts to strengthen prevention and treatment efforts for diabetes and its complications for older adults in this setting.